2014
DOI: 10.1155/2014/385082
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibition Reduces Cardiovascular Responses to Acute Stress in Myocardially Infarcted and Chronically Stressed Rats

Abstract: Previous studies showed that chronically stressed and myocardially infarcted rats respond with exaggerated cardiovascular responses to acute stress. The present experiments were designed to elucidate whether this effect can be abolished by treatment with the angiotensin converting enzyme (ACE) inhibitor captopril. Sprague Dawley rats were subjected either to sham surgery (Groups 1 and 2) or to myocardial infarction (Groups 3 and 4). The rats of Groups 2 and 4 were also exposed to mild chronic stressing. Four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Based on this, Nalivaiko ( 2011 ) proposed that the identification of hypertensive effect preferentially by the tail-cuff method would be due to a more vigorous reaction of the animals stressed to the tail-cuff procedure. Hence, it has been reported that exposure to chronic stressors increases pressor response during acute aversive stimuli (Grippo et al, 2002 , 2006 ; Cudnoch-Jedrzejewska et al, 2010 , 2014 ; Maslova et al, 2010 ).…”
Section: Cardiovascular Responses To Stress: Influence Of Chronicitymentioning
confidence: 99%
“…Based on this, Nalivaiko ( 2011 ) proposed that the identification of hypertensive effect preferentially by the tail-cuff method would be due to a more vigorous reaction of the animals stressed to the tail-cuff procedure. Hence, it has been reported that exposure to chronic stressors increases pressor response during acute aversive stimuli (Grippo et al, 2002 , 2006 ; Cudnoch-Jedrzejewska et al, 2010 , 2014 ; Maslova et al, 2010 ).…”
Section: Cardiovascular Responses To Stress: Influence Of Chronicitymentioning
confidence: 99%
“…Exaggerated pressure response to acute stress challenge has been described in the literature in the animal models of depression (Grippo et al, 2002(Grippo et al, , 2010Nalivaiko, 2011;Cudnoch-Jedrzejewska et al, 2014;McNeal et al, 2014;Benini et al, 2020) but not consistently. In men, social discrimination was related to increased cardiovascular reactivity during a stress session (Richman et al, 2007), while a positive emotional style accelerated the cardiovascular recovery after an acute stressor (Bostock et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, ratos previamente estressados de maneira crônica e posteriormente tratados com captopril, apresentaram uma redução da resposta pressora máxima ocasionada por uma nova exposição ao air-jet stress, além disso, em ratos infartados cirurgicamente, o tratamento com captopril foi capaz de reduzir a resposta taquicárdica máxima ocasionada pelo air-jet stress, tanto no grupo previamente estressado de maneira crônica, quando no grupo nãoestressado (CUDNOCH-JEDRZEJEWSKA et al, 2014). Em conjunto, esses resultados sugerem que a inibição da ECA, e consequente diminuição da formação de Ang-II, pode ser importante na prevenção de alterações cardiovasculares desencadeadas por modelos de estresse.…”
Section: Discussionunclassified